FACTOR ANALYSIS OF WORK-LIFE BALANCE DETERMINANTS AMONG EMPLOYEES OF THE OFFICE OF WOMEN'S EMPOWERMENT AND CHILD PROTECTION IN KENDARI CITY - Nurwati, Nurwati (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to analyze the factors that determine the work-life balance of female employees at the Office of Women’s Empowerment and Child Protection in Kendari City. The variables examined include personality traits, demographic characteristics, job characteristics, the personal meaning of work, and family support. The population of this study consists of all married female employees at the Kendari City Office of Women’s Empowerment and Child Protection, totaling 60 individuals. Due to the limited number of the population, a census approach was applied, whereby all members of the population also served as respondents. The analytical technique used is Exploratory Factor Analysis (EFA), assisted by the IBM SPSS Version 23 software application. The results of the study reveal that three main factors emerged from the factor analysis: job characteristics, personal meaning of work, and family support. Among these, the factor with the most significant influence is the personal meaning of work, indicating that the greater the perceived meaning of work for oneself, the more likely the employees are to maintain their dual roles as both professionals and homemakers. Conversely, family support was found to have the least influence, possibly due to its moderation by personality characteristics. In addition, external influences such as social status issues may also play a role in weakening the effect of family support on work-life balance